Remediation of pharmaceutical pollutants using graphene-based materials - A review on operating conditions, mechanism and toxicology. (November 2022) - Akash, S.; Sivaprakash, Baskaran; Rajamohan, Natarajan; Govarthanan, Muthusamy; Elakiya, B.Tamil
Abstract: Graphene is a high surface area special carbon compound with exceptional biological, electronic and mechanical properties. Graphene-based materials are potential components used in water treatment on different modes and processes. Ibuprofen and ciprofloxacin are two commonly found pharmaceutical contaminants discharged into water bodies from industrial, domestic and hospital sources. Their concentration levels in water bodies are reported in the range of 1 μg/L to 6.5 mg/L and 0.050–100 μg/L respectively. Their toxic effects pose very high risk to the inhabiting organisms. Their ability to resist biodegradation and capacity to bioaccumulate makes the conventional methods less effective in removal. In the present article, treatment of these compounds via three methods, adsorption, photocatalytic degradation and electro–fenton reactions using graphene-based materials along with the methods adopted for synthesis and treatment are reviewed. The uptakes obtained by graphene-derived adsorbents are presented along with the optimal operating conditions. Studies reported complete removal of ibuprofen from wastewater was achieved at 7 pH for 60 min using graphene membrane as adsorbent and uptake of 99% of ciprofloxacin was exhibited for graphene nanoplates/boron nitrate aerogel at a pH of 7 and 60 min. The reduced graphene oxide surface exhibits higher affinity to light adsorption which leads to the formation of photo generated electrons. The future perspectives for improved applications of graphene-based materials and the research gap currently existing are highlighted. Graphical abstract: Image 1 Highlights: Applications of graphene based materials for removal of pharmaceutical components are reviewed. Mechanism of ibuprofen and ciprofloxacin removal is described. Toxicological properties are discussed. Photocatalytic degradation of ibuprofen and ciprofloxacin is described.